Polymorphism of ITS1 and ITS2 regions within and between three distant population of Schizophyllum commune - Boskovic, E; Karaman, M; Galovic, V.; Tamas, I; Venturella, G (Maria Letizia Gargano & Giuseppe Venturella, 2017)
Schizophyllum commune is one of the most widely distributed fungi and can be isolated from all continents, except for Antarctica. It has an important role as wood decomposer since it is mostly found on fallen branches and timber of deciduous trees, but it can also colonize softwood as well as grass silage. As an edible and medicinal mushroom, it has been shown to have various biological functions including anti-tumor, antioxidative and anti-inflammatory activity. Investigation of molecular diversity of this cosmopolitan species is important since it can make us understand what genetic traits are important in maintaining the global success of this species. In this study we analyzed polymorphisms of ITS1 and ITS2 sequences of S. commune populations from Italy, India and China. Italian sequences were obtained from herbaria samples of S. commune sporocarps from University of Palermo while Indian and Chinese sequences were downloaded from UNITE database. ITS1 and ITS2 regions of all analyzed sequences were extracted using ITSx software and variability of these regions was observed separately. Phylogenetic trees were constructed with MEGA 6 software using Neighbour joining method with 1000 Bootstrap replicates. Trees were constructed using ITS1 and ITS2 sequences separately, as well as concatenated ITS1 and ITS2 regions. ITS1 sequences were more variable (21,16%) than sequences of ITS2 region (11,15%). Variability of ITS1 region within Indian, Chinese and Italian population was 15,32; 5,1 and 1,45% respectively, while variation for same populations of ITS2 region was 4,29; 3,43 and 4,72% respectively. All three phylogenetic trees had similar topologies and the best supported tree was one constructed with concatenated ITS1 and ITS2 sequences. Trees based on ITS1 and ITS2 sequences had 4 major clades within S. commune clade, while ITS1/ITS2 tree showed grouping of 6 major clades and several subclades. Majority of sequences from India were grouped in one or two distinct clades in all analyzed trees which are in ...